Activation of peroxymonosulfate by metal (Fe, Mn, Cu and Ni) doping ordered mesoporous Co3O4 for the degradation of enrofloxacin. Issue 5 (9th January 2018) - Deng, Jing; Ya, Chen; Ge, Yongjian; Cheng, Yongqing; Chen, Yijing; Xu, Mengyuan; Wang, Hongyu
Abstract : Various transition metals (Fe, Mn, Cu and Ni) were doped into ordered mesoporous Co3 O4 to synthesize Co3 O4 -composite spinels. Abstract : Various transition metals (Fe, Mn, Cu and Ni) were doped into ordered mesoporous Co3 O4 to synthesize Co3 O4 -composite spinels. Their formation was evidenced by transmission electronic microscopy (TEM), X-ray diffraction (XRD) and Brunauer–Emmett–Teller (BET) analysis. It was found that Co3 O4 -composite spinels could efficiently activate peroxymonosulfate (PMS) to remove enrofloxacin (ENR) and the catalytic activity followed the order Co3 O4 –CuCo2 O4 > Co3 O4 –CoMn2 O4 > Co3 O4 –CoFe2 O4 > Co3 O4 –NiCo2 O4 . Moreover, through the calculation of the specific apparent rate constant ( k sapp ), it can be proved that the Co and Cu ions had the best synergistic effect for PMS activation. The Co3 O4 -composite spinels presented a wide pH range for the activation of PMS, but strong acidic and alkaline conditions were detrimental to ENR removal. Higher reaction temperature could promote the PMS activation process. Sulfate radical was identified as the dominating reactive species in Co3 O4 -composite spinel/PMS systems through radical quenching experiments. Meanwhile, the probable mechanisms concerning Co3 O4 -composite spinel activated PMS were proposed.